Discovery of an autophagy inducer J3 to lower mutant huntingtin and alleviate Huntington’s disease-related phenotype - Jiahui Long; Xia Luo; Dongmei Fang; Haikun Song; Weibin Fang; Hao Shan; Peiqing Liu; Boxun Lu; Xiao-Ming Yin; Liang Hong; Min Li (figshare, 2022)
Abstract Huntington’s disease (HD) is a neurodegenerative disorder caused by aggregation of the mutant huntingtin (mHTT) protein encoded from extra tracts of CAG repeats in exon 1 of the HTT gene. mHTT proteins are neurotoxic to render the death of neurons and a series of disease-associated phenotypes. The mHTT is degraded through autophagy pathway and ubiquitin–proteasome system (UPS). This study identified a small molecule, J3, as an autophagy inducer by high-content screening. The results revealed that J3 could inhibit mTOR, thus promoting autophagic flux and long-lived protein degradation. Further, J3 selectively lowered the soluble and insoluble mHTT but not wild type HTT levels in cell models. The HdhQ140 mice showed reduced HD-associated activity and loss of motor functions. However, administration of J3 showed increased activity and a slight improvement in the motor function in the open-field test, balance beam test, and rotarod tests. Furthermore, in vivo studies revealed that J3 decreased T-HTT and misfolded protein levels in the striatum and increased the levels of the medium spiny neuron marker DARPP-32. In addition, J3 showed good permeability across the brain-blood barrier efficiently, suggesting that J3 was a promising candidate for the treatment of HD.
Keywords: Biochemistry; Cell Biology; Genetics; Molecular Biology; Neuroscience; Physiology; Chemical Sciences not elsewhere classified